The Causes of Grammatical Errors Made by EFL Students in Writing Essay - Sari, Resty Maya (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
Writing an essay is one of challenging assignment for students, even an English department student get confused in writing a descriptive or narrative essay. Hence, there are many students who make some grammatical errors in writing an essay. This study aimed to investigate the causes of grammatical errors made by sixth semester English Study Program students in writing essay. The design of this study was qualitative with descriptive method. The researcher took 66 students as the subject of the study and open ended questionnaire as the instrument. The finding of this study showed that there were three causes of grammatical errors made by students, namely; carelessness, first language, and translation and the dominant cause was translation. The researcher also found that another causes of grammatical error were lack of vocabulary and lack of grammar. Mostly the students made error because of the translation method by using google translate or online dictionary. It can be concluded that the causes of grammatical error made by the students in writing essay at sixth semester students in the English Education Study Program at University of Muhammadiyah Bengkulu were carelessness, first language, and translation. Moreover, the dominant cause of misformation error done by the students was translation. It is suggested for the students to practice writing more frequently to minimilize the errors in writing essay. It will be better if the students did not use google translate or online dictionary much. For lecturer of writing subject, the results of this study can be one form of evaluation that can be used to know the students’ causes of grammatical errors in order to find out some relevant strategies to overcome the causes. By overcoming the causes of misformation and giving motivation to the students to write carefully, the lecturers can carry out better quality teaching and learning activities especially in writing skill.